the Perlindungan Privasi dan Data Pribadi Konsumen Pada Online Marketplace Qualitva.id: Protection of Consumer Privacy and Personal Data on the Qualitva.id Online Marketplace - M Guntur Guntur (Institute of Information Technology and Social Science (IITSS), 2022)
The online market system is one form of development in e-commerce activities. The online market system provides facilities for shopping online with various services aimed at making it easier for online consumers or e-consumers. However, on the other hand, services that make this easier also carry potential threats to personal data and online consumer privacy. This research focuses on discussing personal data protection and privacy for e-consumers in online market systems, using normative or legal research methods. The research approaches used include the Statute Approach, Conceptual Approach, Case Approach, and Comparative Approach. The research results show that the development of e-commerce in Indonesia has experienced rapid progress, supported by state initiatives such as the